Heating potential of undeveloped geothermal water intakes in Poland in the context of sustainable development and air protection - Ewelina Łukasiewicz; Moein Shamoushaki (Water Resources and Industry, 2022)
Poland has significant geothermal water resources and the study presents a list of 29 undeveloped but existing intakes of ready-thermal waters with temperatures ranging from 21 to 86 °C. In this study, important issues related to the hitherto unused intakes of geothermal waters will be discussed in a comprehensive manner: a review has been made with regard to the location of geothermal water resources in Poland, where there are already wells, but not yet exploited – list of all undeveloped geothermal water intakes. Estimated calculations were made for 29 wells, of Thermal Power [MW] and Thermal Energy [GWh/year] and estimated Exergy [kJ/kg] analysis for selected intakes. In the context of air protection, calculations were made related to the estimated reduction of harmful air pollutants, if the geothermal intakes presented in the article were to be used. Presents the results for coagulation for water from a selected geothermal water intake, from which it was possible to remove the total iron content from the water with high efficiency. This is the proposed method of treating geothermal water, supported by the results of the researcher's own research. The thermal energy that these sources can generate amounts to a total of approximately 247.5 [GWh/year]. Moreover, this energy would allow to heat about 8250 single-family houses, covering a total area of 350,000 square meters. The problem of geothermal water quality was discussed and the results were presented after it had been subjected to the coagulation process. Coagulation has been proposed as an effective method to remove undesirable compounds from geothermal water before it enters the installation. A satisfactory total iron removal effect at the level of 99% was obtained thanks to the use of highly polymerized aluminum coagulants in combination with filtration.